Этнокультура: русско-удмуртские связи: избранные труды / Н. В. Витрук - Витрук Николай Васильевич (Удмуртия, 2007)
Экземпляры: Кр (2008) / Инвентарный номер: 37906 / Цена: / Сис.шифр: 83.3(2Рос=Рус) / Авт.знак: В 54 / ГРНТИ: 17.01.09 / ББК: 83.3(2Рос=Рус)